Money mystery - Chong, Grace D.; Doctolero, Elizabeth Parrocha (Mandaluyong City : OMF Literature, 2006)
Teo explores an old abandoned house in search of a missing treasure.
Keywords: Treasure -- Juvenile fiction; Children's stories, Filipino